COVID-19: Effects on Eye in Bangladesh (Bangladesh Medical Journal, 2020)
COVID-19 is a contagious disease which can spread person to person mainly by respiratory droplet from infected person and contact by contaminated objects or body limbs through the routes nose, mouth, and eyes. To find out the ocular manifestations that are found in Bangladesh during COVID-19 pandemic this descriptive type of cross-sectional study was conducted to detect the ocular infection and its manifestation among patients admitted at different COVID-19 dedicated hospitals. Total 26 doctor’s (Eye Specialists, ICU Consultants, ICU Residents/ Medical Officers, Consultants of other Specialities, Medical Officers/ Residents) observational and examination findings were recorded in this study who have already completed one or more roster [07 days] duties in Corona Dedicated hospitals to treat the COVID-19 affected patients directly. Total 3,678 patients information from different hospitals were collected and interviews were taken directly or over telephone from the participants. Data collected from the participants based on the observations of physicians during COVID roster duties in different corona dedicated hospitals. Age sex and ocular signs and symptoms found in patients during hospitalization were recorded. Total 08 (eight) Corona dedicated hospitals; one Medical University, five tertiary level Govt. hospitals, one private Medical College hospital and one largest Isolation center of South-Asia were included as study place. Among the cases 66.2% were male and 33.8% female. Maximum patients were in age group 40-60 years [40%] and minimum of them were above 70 years [10%]. Ocular manifestations found in 48 cases and.30 in suspected, total 78 cases found with ocular manifestations. Total 2.121% patients hade ocular manifestations in confirmed and suspected cases. In COVID confirmed cases 1.316% patients hade ocular manifestations. In conclusion, we found several ocular manifestations in patients who are hospitalized as COVID-19 patients. Moreover, the ocular involvement could be the presenting finding of disease. Further studies are required in Bangladesh and this information may be valuable for future studies.Bangladesh Med J. 2020 May; 49(2) : 14-18